Manajemen Administrasi Berbasis Kompetensi: Strategi Penguatan Lembaga PAUD - Siti Aminah; Ahmad Riyadi; Agung Prasetyo; Sony Kuswandi; Devi Sulaeman (CV. Creative Tugu Pena, 2024)
Efficient and competency-based educational administration management is an important key in improving the operational quality of educational institutions, especially at the PAUD level, which functions to ensure the smooth learning process and service to the community. This community service activity was carried out at the Merpati PAUD Institute, Kutawaluya District with the aim of increasing the capacity of PAUD administration and management staff in the Kutawaluya subdistrict area through the Asset-Based Community Development (ABCD) approach. This approach focuses on utilizing local potential to strengthen administrative management and increase work efficiency. The aim of this activity is to develop the competence of administrative staff and teachers in more efficient competency-based administrative management, as well as building community solidarity in supporting better PAUD management. The methods used include identifying needs through focus group discussions (FGD), training, mentoring and participation-based evaluation. Activities began with local resource mapping, followed by technical training on administrative management and the use of simple technology. Mentoring is carried out intensively to ensure the implementation of training results in the field. The results of the activity show an increase in the understanding of administrative staff and teachers regarding the importance of competency-based administrative management, as well as positive changes in a more professional work culture. The implication is improving the quality of PAUD management which can strengthen public trust in the institution and create a sustainable social impact in the management of early childhood education.